Hindutva for our times - Sharma, Arvind (Routledge, 2025)
"This book studies Hindu nationalism and deliberates on the forms Hindu self-assertion might take in the future. It examines the intersection of Hindu nationalism with the contemporary reality of India, as represented by a religiously plural society with a secular state, which possesses a social system characterised by caste, and one whose vision has been shaped by a mainstream version of Indian history. The ideology of Hindutva has had two major orientations-of how Hindus should relate to each other, and how Hindus should relate to the followers of other religions. The author provides a new orientation to both these dimensions of Hindutva ideology. A unique contribution, this book will be an essential read for scholars and researchers of religion studies, history, postcolonialism, nationalism, pluralism, Indian political thought, Indian history, caste studies, political science, Hindu studies, Hindusim, sociology and political ideology, and South Asian studies"--